Financial constraints and production efficiency: A case from rice growers in drought prone areas of Indonesia. Issue 1 (5th February 2018) - Khanal, Aditya R.; Regmi, Madhav
Abstract : Purpose: The purpose of this paper is to study the production and efficiency of rice growers in drought prone areas with special attention given to economic and financial factors. Design/methodology/approach: The authors use a parametric stochastic frontier approach and a non-parametric data envelopment analysis. Findings: The study found that financial and liquidity constraints negatively influence production efficiency while off-farm work positively influences efficiency in drought prone areas. Originality/value: Many biotic and abiotic factors affect the production efficiency of rice growers. Among abiotic stress, drought is the strongest constraint affecting nearly one third of the total rice area in Asia and causing significant economic losses. Farmers' economic conditions and financial constraints further exacerbate the situation. However, very few studies have analyzed the efficiency in drought prone areas and the influence of economic and financial factors. This study contributes to in this regard by augmenting economic and financial factors in the efficiency estimation of drought prone areas using parametric and non-parametric approach.